A case of topical imiquimod induced fatigue. (17th November 2022) - Raman, Justin; Bisbee, Elizabeth; Missall, Tricia A.; Saikaly, Sami K.
Abstract: Topical imiquimod is used for a variety of common dermatologic lesions, including melanoma in-situ . As an immunomodulator, it is relatively well tolerated with minimal side effects, including scaling, erythema, and edema. Here we present a rare systemic adverse effect, where our patient experienced debilitating severe fatigue when applying imiquimod to a single lesion. Clinicians should be mindful of this side effect and counsel patients appropriately.